Peer review of the pesticide risk assessment of the active substance tritosulfuron - Álvarez, Fernando; Arena, Maria; Auteri, Domenica; Batista Leite, Sofia; Binaglia, Marco; Castoldi, Anna Federica; Chiusolo, Arianna; Cioca, Ana‐Andreea; Colagiorgi, Angelo; Colas, Mathilde; Crivellente, Federica; De Lentdecker, Chloe; et al. (EFSA journal, 2023)
The conclusions of the European Food Safety Authority (EFSA) following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State, Slovenia, and co‐rapporteur Member State, Austria, for the pesticide active substance tritosulfuron are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012, as amended by Commission Implementing Regulation (EU) No 2018/1659. The conclusions were reached on the basis of the evaluation of the representative uses of tritosulfuron as a herbicide on spring and winter cereals, spring cereals with undersown grasses and maize (field uses). The reliable end points, appropriate for use in regulatory risk assessment, are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are reported where identified.